2021
DOI: 10.1093/mnras/stab767
|View full text |Cite
|
Sign up to set email alerts
|

The most massive white dwarfs in the solar neighbourhood

Abstract: We present an analysis of the most massive white dwarf candidates in the Montreal White Dwarf Database 100 pc sample. We identify 25 objects that would be more massive than 1.3 M⊙ if they had pure H atmospheres and CO cores, including two outliers with unusually high photometric mass estimates near the Chandrasekhar limit. We provide follow-up spectroscopy of these two white dwarfs and show that they are indeed significantly below this limit. We expand our model calculations for CO core white dwarfs up to M = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…More recently, Blouin, Daligault & Saumon (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallizing white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultramassive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka, Vennes & Ferrario 2020;Kilic et al 2021).…”
mentioning
confidence: 90%
“…More recently, Blouin, Daligault & Saumon (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallizing white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultramassive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka, Vennes & Ferrario 2020;Kilic et al 2021).…”
mentioning
confidence: 90%
“…These stars play a key role in ★ The cooling sequences are publicly available for download at http://evolgroup.fcaglp.unlp.edu.ar/TRACKS/tracks.html † E-mail: maria.camisassa@colorado.edu our understanding of type Ia Supernova explosions, the occurrence of physical processes in the asymptotic giant-branch (AGB) phase, the existence of high-field magnetic white dwarfs, and the occurrence of double white dwarf mergers (Dunlap & Clemens 2015;Reindl et al 2020). The observation of ultra-massive white dwarfs has been reported in several studies in the literature (Mukadam et al 2004;Nitta et al 2016;Gianninas et al 2011;Kleinman et al 2013;Bours et al 2015;Kepler et al 2016;Curd et al 2017;Kilic et al 2021;Hollands et al 2020;Caiazzo et al 2021;Miller et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of fast rotation rates, unique chemical composition, high mass, and high incidence of magnetism in hot DQ white dwarfs favor a double white dwarf merger origin for the formation of these stars (Dunlap & Clemens 2015;Coutu et al 2019). Kilic et al (2021) presented an analysis of the ultramassive (M ≥ 1.3M ) white dwarf candidates in the Montreal White Dwarf Database (MWDD, Dufour et al 2017) 100 pc sample, and identified four out- liers in transverse velocity, four likely magnetic white dwarfs (one of which is also an outlier in transverse velocity), and one with rapid rotation. They concluded that at least 32% of the 25 ultramassive white dwarfs in that sample are likely double white dwarf merger products.…”
Section: Introductionmentioning
confidence: 99%
“…There remains three additional confirmed or suspected magnetic white dwarfs known in the Kilic et al (2021) ultramassive white dwarf sample; SDSS J221141.80+113604.5 is a DAH with weak Hα and Hβ features, SDSS J225513.48+071000.9 has a DClike spectrum that shows broad unidentified features, and WD J010338.56−052251.96 (G270-126) is a DAH: (Tremblay et al 2020). We refer to these systems as J2211+1136, J2255+0710, and J0103−0522, respec-tively.…”
Section: Introductionmentioning
confidence: 99%